Distinct functions of human RecQ helicases during DNA replication - Urban, Vaclav; Dobrovolna, Jana; Janscak, Pavel (Bioorganic chemistry, 2017)
DNA replication is the most vulnerable process of DNA metabolism in proliferating cells and therefore it is tightly controlled and coordinated with processes that maintain genomic stability. Human RecQ helicases are among the most important factors involved in the maintenance of replication fork integrity, especially under conditions of replication stress. RecQ helicases promote recovery of replication forks being stalled due to different replication roadblocks of either exogenous or endogenous source. They prevent generation of aberrant replication fork structures and replication fork collapse, and are involved in proper checkpoint signaling. The essential role of human RecQ helicases in the genome maintenance during DNA replication is underlined by association of defects in their function with cancer predisposition.
Keywords: Neoplasms; nádory; nestabilita genomu; helikasy RecQ; lidé; RecQ Helicases; replikace DNA; DNA Replication; Genomic Instability; Humans